Proteomic analysis identified proteins that are differentially expressed in the flavonoid and carotenoid biosynthetic pathways of Camellia Nitidissima flowers - Xing-Wen Zhou; Xiao-Xia Ye; Bao-Jian Ye; Shi-Hong Yan; Hai-Bin Hu; Qiu-Yuan Xu; Xiong Yao; He-Xia Liu; Bo Li; Yi-Qing Xie; Zhong-Jian Liu (BMC Plant Biology)
Abstract Background Camellia nitidissima Chi is a popular ornamental plant because of its golden flowers, which contain flavonoids and carotenoids. To understand the regulatory mechanism of golden color formation, the metabolites of C. nitidissima petals at five different developmental stages were detected, a proteome map of petals was first constructed via tandem mass tag (TMT) analysis, and the accuracy of the sequencing data was validated via parallel reaction monitoring (PRM). Results Nineteen color components were detected, and most of these components were carotenoids that gradually accumulated, while some metabolites were flavonoids that were gradually depleted. A total of 97,647 spectra were obtained, and 6,789 quantifiable proteins were identified. Then, 1,319 differentially expressed proteins (DEPs) were found, 55 of which belong to the flavonoid and carotenoid pathways, as revealed by pairwise comparisons of protein expression levels across the five developmental stages. Notably, most DEPs involved in the synthesis of flavonoids, such as phenylalanine ammonium lyase and 4-coumarate-CoA ligase, were downregulated during petal development, whereas DEPs involved in carotenoid synthesis, such as phytoene synthase, 1-deoxy-D-xylulose-5-phosphate synthase, and β-cyclase, tended to be upregulated. Furthermore, protein‒protein interaction (PPI) network analysis revealed that these 55 DEPs formed two distinct PPI networks closely tied to the flavonoid and carotenoid synthesis pathways. Phytoene synthase and chalcone synthase exhibited extensive interactions with numerous other proteins and displayed high connectivity within the PPI networks, suggesting their pivotal biological functions in flavonoid and carotenoid biosynthesis. Conclusion Proteomic data on the flavonoid and carotenoid biosynthesis pathways were obtained, and the regulatory roles of the DEPs were analyzed, which provided a theoretical basis for further understanding the golden color formation mechanism of C. nitidissima.